THEORETICAL AND PRACTICAL ASPECTS OF TEACHING ECONOMIC KNOWLEDGE AND SKILLS TO STUDENTS IN GRADES 5–6 (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the theoretical and practical aspects of teaching economic knowledge and skills to students in grades 5 - 6. The author justifies the need for the formation of economic literacy from an early age in modern society. The article describes ways to organize economic education based on person-oriented, activity-based and integrative approaches. Also, methodological recommendations are given for instilling economic concepts in children through practical exercises, role-playing games, project work and digital tools. These knowledge and skills play an important role in the formation of critical thinking, planning, responsibility and financial culture in students.